(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
This article explores the importance of differentiated instruction and individualized approaches in teaching English. By catering to the diverse needs, abilities, and learning styles of students, educators can create more inclusive and effective learning environments. Various strategies, including content differentiation, personalized learning plans, and adaptive technologies, are discussed to enhance student engagement and improve language proficiency.